PEMBUATAN SISTEM PEMANTAUAN PH DAN PPM AIR PADA HIDROPONIK BERBASIS IoT - Agus Hermanto; Tony Ahmad Husein Al Mubarok; Agung Kridoyono (Program Studi Sistem Informasi, Universitas Banten Jaya, 2025)
The reduction in agricultural land due to being converted into housing and urban areas means that the amount of food production is decreasing. Based on the problems above, the author offers an innovation to overcome the problem of food security through